Analysis of tax compliance among crypto actors in Indonesia: The role of digitalization, rates, and audits - Saputra, Kelvin; Tarmidi, Deden (WIM Solusi Prima, 2025)
This study aims to examine and analyze the role of tax digitization, tax rates, and tax audit in improving the compliance of individual taxpayers. The research object is crypto traders in Indonesia. This study utilizes primary data obtained using Slovin's formula, resulting in a sample of 100 respondents determined through purposive sampling. The collected data is then analyzed for testing. The data analysis method employed is multiple regression analysis, processed using the SmartPLS application to obtain relevant and accurate results. In the research that has been conducted, the results indicate that tax digitalization and tax rates have a positive influence on taxpayer compliance. However, tax audits do not affect taxpayer compliance.